Pemanfaatan Quizizz Sebagai Alat Evaluasi Berbasis Mapping pada Mahasiswa Pendidikan Ekonomi - Yuri, Cicia Oktri; Fadhilah, Farhan; Putri, Desi Armi Eka (Indo-MathEdu Intellectuals Journal, 2025)
In an increasingly advanced digital era, AI offers innovative solutions that can improve students' understanding and skills. This research aims to explore the effects of artificial intelligence (AI) in helping economic education students apply concept mapping techniques in economics courses. Methodology The study conducted was a descriptive research using a qualitative approach. Data obtained from literature study. The research results show that the use of AI in the concept mapping process allows students to organize information visually and systematically, thereby increasing their understanding of the subject matter. In addition, AI also provides fast and accurate feedback, which helps students identify errors and improve their understanding. These findings emphasize the importance of integrating technology in economics education to create a more effective and engaging learning experience. This research identified key benefits of using AI, such as personalization of learning experiences, improved memory, and development of critical thinking skills. However, it also underscores the challenges students face, including dependence on technology, lack of digital literacy, data privacy issues, and gaps in technology access.